2012
DOI: 10.2903/j.efsa.2012.2642
|View full text |Cite
|
Sign up to set email alerts
|

Scientific Opinion on the safety evaluation of the active substances, sodium borohydride and palladium acetate for use in active food contact materials

Abstract: This scientific opinion of EFSA deals with the risk assessment of sodium borohydride (CAS No 16940-66-2 and FCM substance No 981), and palladium acetate , reduced to palladium FCM substance No 993) in the plastic during the manufacturing process, when used in combination as an oxygen absorbing system in food contact materials. The CEF Panel considers that palladium is non genotoxic and a low exposure to palladium resulting from a concentration up to 0.05 mg/kg food is not of toxicological concern.In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
0
4
0
2
Order By: Relevance
“…Sodium borohydride was also evaluated as active FCM substance (EFSA CEF Panel, 2012b). In that case, the CEF Panel concluded that there is no safety concern for the consumer when the sodium borohydride is only used behind a plastic layer to prevent direct contact with the packaged food.…”
Section: General Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Sodium borohydride was also evaluated as active FCM substance (EFSA CEF Panel, 2012b). In that case, the CEF Panel concluded that there is no safety concern for the consumer when the sodium borohydride is only used behind a plastic layer to prevent direct contact with the packaged food.…”
Section: General Informationmentioning
confidence: 99%
“…Boric acid is authorised as a monomer and additive for plastic materials and articles in contact with foods (Regulation (EU) No 10/2011) with a combined specific migration limit (SML) with other substances containing boron of 6mg/kg (expressed as boron) (FCM Substance No 584). Sodium borohydride was also evaluated as active FCM substance (EFSA CEF Panel, 2012b). In that case, the CEF Panel concluded that there is no safety concern for the consumer when the sodium borohydride is only used behind a plastic layer to prevent direct contact with the packaged food.…”
Section: General Informationmentioning
confidence: 99%
“…Palladium was considered to be non genotoxic and of no toxicological concern under a low exposure level resulting from a concentration up to 50 µg/kg food in a previous evaluation (EFSA CEF Panel, 2012). The active article is designed as a gas permeable but liquid impermeable laminated pad, which is placed within a cap or closure or as an adhesive label on tray lids.…”
mentioning
confidence: 99%
“…The specific migration of palladium metal into conventional food simulants was not detected at the limit of quantification of 0.6 µg/kg. Palladium was considered to be non genotoxic and of no toxicological concern under a low exposure level resulting from a concentration up to 50 µg/kg food in a previous evaluation (EFSA CEF Panel, 2012). Based on these previously drawn conclusions and given the intended conditions of use leading to non-detectable migration, the CEF Panel concluded that the active substances palladium and hydrogen do not raise a safety concern for the consumer when used as an oxygen scavenger in packages for foods and beverages at room temperatures or below.…”
mentioning
confidence: 99%
“…La forma más tradicional de sintetizar NPa de plata (NPaAg) es a través de la reducción o síntesis química, donde los iones Ag + se reducen para nuclearse y formar nanoestructuras de Ag o . El agente reductor más utilizado en las síntesis químicas es el borohidruro de sodio, el cual es tóxico para el medio ambiente y un agente considerado peligroso para el personal que lo manipula [81]. Por otra parte, para que las NPa se mantengan estables en suspensión y no precipiten, es necesario utilizar algún agente estabilizante que las recubra (capping).…”
Section: Síntesis Ecocompatibles De Nanopartículas De Plataunclassified